Expert Systems for Scanner Data Environments The Marketing Workbench Laboratory Experience - McCann, John M.; Gallagher, John P. (International Series in Quantitative Marketing, 1990)
This book is about the role of expert systems in marketing, particularly in the consumer goods industry. Section I describes the changing nature of consumer marketing and presents the rationale and need for expert systems. The remainder of the book combines a tutorial on expert systems with a series of expert system prototypes. The tutorial material is presented in three places. First, section II is devoted to introducing expert systems in general. Chapter 3 provides a general introduction to the topic, which is continued in chapter 4 where a small expert system (the Promotion Advisor) is used to illustrate the important features of a backward-chaining, rule-based system. The promotion theme is extended in chapter 5 where a larger system is presented. The material in all three of these chapters was designed as an introduction and tutorial on the most common technology for building applied expert systems: the backward-chaining, rule-based inference engine. Tutorial material is also contained in the body of the chapters that describe the prototypes. This material is usually in the form of sample rules and a description of the process for applying the rules. The third location of the expert system material is in chapters that follow discussions of the prototypes. Chapter 7 is a technical chapter on the coupling of expert systems to traditional systems